LANGUAGE AND IDENTITY - Азимова Севара Абдулла кизи; Халикова Назира Мухаммаджон кизи (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Language is not just a tool for communication; it is deeply intertwined with both individual and collective identities. The relationship between language and identity is multi-layered, evolving, and culturally significant, encompassing elements of personal self-expression, social roles, and cultural belonging. It serves as a mirror to the experiences, values, and beliefs of individuals, while also marking the boundaries between different groups, creating distinctions based on ethnicity, nationality, and social class. From a sociolinguistic perspective, language plays a fundamental role in shaping how people view themselves and how they are perceived by others.